2009
DOI: 10.1007/s10750-009-9941-3
|View full text |Cite
|
Sign up to set email alerts
|

Movement behaviour of the small benthic Rhine sculpin Cottus rhenanus (Freyhof, Kottelat & Nolte, 2005) as revealed by radio-telemetry and pit-tagging

Abstract: From February 2006 to June 2007, we followed the movement patterns of the Rhine sculpin (Cottus rhenanus) by combining short-term radiotelemetry (n = 10 radio-tagged sculpin with a miniature 0.5-g transmitter) and long-term individual (PIT-tag) mark-recapture (n = 452 PIT-tagged sculpin during six removal electric fishing operations) studies in a small tributary of the River Meuse, Belgium. During a 25-to 27-day period, the radio-tracked sculpin displayed various mobility patterns, showing frequent movement fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…radio and PIT-telemetry, allowed a better understanding of the movement patterns and spatial distribution of stocked and native trout through intensive tracking of a small number of radio-tagged fish over a short time scale and continuous monitoring of movements and microhabitat use by PIT-telemetry. As pointed out by Ovidio et al (2009) gaps in the fish behaviour can be closed using complementary methodologies. This study also confirmed previous observations following distinct methodologies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…radio and PIT-telemetry, allowed a better understanding of the movement patterns and spatial distribution of stocked and native trout through intensive tracking of a small number of radio-tagged fish over a short time scale and continuous monitoring of movements and microhabitat use by PIT-telemetry. As pointed out by Ovidio et al (2009) gaps in the fish behaviour can be closed using complementary methodologies. This study also confirmed previous observations following distinct methodologies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The limited potential for colonization from other populations (the 'rescue effect', Hanski 1999) may help to explain why E. triquetra and other Epioblasma species are highly imperiled (Nature Serve 2009). Table 3 Results from the ANCOVA analyses that examined whether there were differences in the relationship between the predictor variable (e.g., study design parameters: spatial extent of the study, study duration and recapture rate) and the maximum displacement distances for darters and sculpins Ovidio et al (2009) …”
Section: Discussionmentioning
confidence: 99%
“…Japanese fluvial sculpin, Cottus pollux Günther 1873: Natsumeda, 2001;C. bairdii: Petty & Grossman, 2004;Rhine sculpin, Cottus rhenanus Freyhof, Kottelet & Nolte 2005: Ovidio et al, 2009. They have an extremely reduced swim-bladder and are known for their benthic and cryptic behaviour (e.g.…”
Section: Study Speciesmentioning
confidence: 99%
“…: Breen et al, 2009;Hudy & Shiflet, 2009;Ovidio et al, 2009). Between-individual differences in the range of movements can be extreme.…”
Section: Study Speciesmentioning
confidence: 99%